The effect of Salmonella autogenous vaccination on serotype surveillance, recovery, and phenotypic characteristics - Robinett, Emily (Kansas State University, 2022)
Salmonella enterica is a major cause of foodborne illnesses around the world and is commonly caused by contaminated poultry food products. Currently, the poultry industry utilizes numerous protocols to mitigate the control of Salmonella prevalence and transmission within various operations. Autogenous vaccines allow for the customized vaccination of poultry in different farms, but the selection of an appropriate vaccine formulation can be challenging to narrow down based on the isolates derived from each location. Salmonella surveillance studies can aid in the identification of Salmonella serotypes that are prevalent throughout a company or farm, and the use of various phenotyping methods can aid in identifying variations between isolates. For this study, four large poultry operations in the US were analyzed for changes in the recovery, prevalence, and phenotype of Salmonella over a four-year period following the implementation of autogenous vaccination program. Bacterial phenotypic characteristics used in the study were arginine dihydrolase, citrate utilization, acetoin production, d-sorbitol fermentation, inositol utilization, and biofilm formation for the selection of the autogenous vaccine formulations. In the four-year study period, the overall prevalence of Salmonella decreased in both the hatcheries and the processing plants of the study sites. Serotype S. Heidelberg represented 6.7% of isolates in the processing plants in 2017, but within a year after the implementation of the autogenous vaccination, it was not isolated in any of the study sites. The prevalence of serotypes S. Enteritidis and S. Typhimurium decreased between 2017 and 2020, but S. Infantis and S. Kentucky increased. Salmonella Kentucky was not included in the autogenous vaccine formulations, which could explain the increased prevalence. There was no difference in the prevalence of phenotypic indicator, arginine dihydrolase, suggesting that it would not be useful when monitoring the efficacy of autogenous vaccines. However, the prevalence of phenotypic indicators citrate utilization, d-sorbitol fermentation, inositol utilization and biofilm formation varied throughout the study in response to the vaccine formulation, indicating that they may be useful when monitoring the efficacy of autogenous vaccines. Future studies should be conducted to determine whether the phenotypic characteristics of autogenous Salmonella vaccines are related to the vaccine efficacy.
Keywords: Phenotype; Poultry; Autogenous vaccine; Surveillance; Salmonella